Enhancing Environmental Performance through Green HRM and Employee Green Behavior: Evidence from Hospitality Industry - Laia, Lain Masa; Palupiningtyas, Dyah (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the impact of Green Human Resource Management (GHRM) on Environmental Performance, with Employee Green Behavior acting as a mediating variable within the hospitality industry in Semarang. Data were collected through questionnaires distributed to 200 permanent hotel employees selected using purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with AMOS 24 software. The findings reveal that: (1) GHRM has a positive and significant effect on Environmental Performance (β = 0.386; C.R. = 4.725; p < 0.05); (2) GHRM positively and significantly influences Employee Green Behavior (β = 0.452; C.R. = 5.138; p < 0.05); (3) Employee Green Behavior exerts a positive and significant effect on Environmental Performance (β = 0.394; C.R. = 4.892; p < 0.05); and (4) Employee Green Behavior partially mediates the relationship between GHRM and Environmental Performance (indirect effect = 0.178; C.R. = 3.967; p < 0.05). The research model competes well with empirical data (CMIN/DF = 2.341; GFI = 0.921; AGFI = 0.903; CFI = 0.947; TLI = 0.938; RMSEA = 0.067). These findings underscore the critical role of integrating environmental considerations into human resource management practices to enhance hotels' environmental performance by fostering pro-environmental behavior among employees.